Distillation technique and its impact on the criticism and formation of contemporary painting (Journal of the College of Basic Education, 2023)
The technique known as distillation in contemporary global formation is one of the most important transformations in the art of painting, and it is a phenomenon that has prevailed since the fifties of the last century until today. Abstract expressionism has flourished in painting in general, especially painting in the style of distillation. It is a manifestation of the prevailing scientific spirit of the era and that all values and symbols must be excluded from the spirit of art, whether social or political, religious or commercial!!, Is what the Impressionists reached of the combination of form, image and parts is “abstract art”? And that modern art reached this truth?This research discussed and linked three elements that cannot be fragmented so that we can stand on the mechanics of the success of the works of distillation artists and the fame of the work and style of the American artist Jackson Pollock in distillation. These three can be summarized as follows: By pouring it and dripping it back and forth over the surface of the painting and using many different materials such as pebbles, cigarette butts, etc., and this artist is Pollock, but this alone is not enough for the artist or the method to gain all this fame and prosperity, unless there are parties that have their artistic weight embracing it, that is, there is the press or the media Or in short (schools of criticism) that supported and encouraged this idea, and this is what actually happened. Pollock lived with two of the most famous critics in America, Greenberg and Rosenberg. Greenberg's direction is strongly associated with his support for abstract expressionism and strongly pushes the need for abstract art to be a means of resisting interference in politics and commerce. In art, he is the owner of the principle (that art should not be sold), while the other trend is Rosenberg, and he calls that modern abstract art is an image that characterizes the modern world, in a society facing a crisis in contemporary culture. Like all his aspirations, he found that art (immediate) or the unconscious is the solution to this crisis in culture, society and politics, despite the existence of two critical opinions in the contemporary artistic community. Pollock took both directions together as his approach, or that the two approaches matched his approach. The third element is society, and here It will be precisely the New York society in America, as Europe is engulfed in its war, most of the cities are destroyed, and many of the world’s artists went to this city to be the new art lung after Paris and Rome, and in the post-World War II period, the feeling of physical and emotional liberation and the sense of release spread, and it affected a lot on Exhausted by the war, Jackson Pollock introduced towards abstract expressionism his new style and eventually forced critics to call the style (distillation), where he received the bustling city society of banks, tall buildings, stock exchanges and various art galleries, these works and considered expressive of his feelings and hustle.With the presence of these three elements (the artist, criticism, and society), the painting style continued by dripping, dripping, or pouring, flourishing, branching, and living to this day.